Electronic Mediation in Divorce Cases at the Religious Court of Probolinggo City from the Perspective of Maqasid Al-Syariah - Alvan Fathony; Ummu Hani Auliah (At-Tafkir, 2025)
Maintaining harmony within the marital environment is essential for the stability of any household. However, over time, various challenges may arise that can lead to divorce. This study aims to examine the strategies employed in electronic mediation for divorce cases at the Probolinggo City Religious Court, with particular attention to the implementation of PERMA No. 1 of 2016, and to analyze these practices from the perspective of Maq??id Al-Syar?ah. Employing a qualitative research method, this study was conducted at the Probolinggo City Religious Court, where electronic mediation has been implemented either fully or partially online, in line with PERMA No. 1 of 2016 Article 6(2), before the issuance of PERMA No. 3 of 2022. The findings reveal that the success of electronic mediation heavily relies on the active participation and cooperation of the involved parties. Legally, the study identifies the need for more detailed regulations to standardize mediation procedures. Socially, while access to justice has improved, challenges remain due to low public trust. Institutionally, enhancing mediators’ competencies and upgrading technological infrastructure are imperative. Electronic mediation increases the efficiency of Islamic justice; however, clear legal provisions are necessary to ensure its validity. Although this method offers flexibility, it may diminish the emotional dimension crucial to reconciliation. Psychologically, it reduces the pressure on parties but may impair effective communication. Therefore, the implementation of electronic mediation must balance legal, social, and psychological considerations. Full commitment from all parties is essential to avoid negative outcomes. The mediator’s role as facilitator and intermediary—not decision-maker—requires strong collaboration to achieve desired resolutions. Furthermore, the principles of Maq??id Al-Syar?ah align with contemporary practices, emphasizing community welfare and solutions that conform to Sharia values.